Zebrafish Cancer Predisposition Models - Kobar, Kim; Collett, Keon; Prykhozhij, Sergey V.; Berman, Jason N. (Frontiers in Cell and Developmental Biology, 2021)
Cancer predisposition syndromes are rare, typically monogenic disorders that result from germline mutations that increase the likelihood of developing cancer. Although these disorders are individually rare, resulting cancers collectively represent 5-10% of all malignancies. In addition to a greater incidence of cancer, affected individuals have an earlier tumor onset and are frequently subjected to long-term multi-modal cancer screening protocols for earlier detection and initiation of treatment. In vivo models are needed to better understand tumor-driving mechanisms, tailor patient screening approaches and develop targeted therapies to improve patient care and disease prognosis. The zebrafish (Danio rerio) has emerged as a robust model for cancer research due to its high fecundity, time- and cost-efficient genetic manipulation and real-time high-resolution imaging. Tumors developing in zebrafish cancer models are histologically and molecularly similar to their human counterparts, confirming the validity of these models. The zebrafish platform supports both large-scale random mutagenesis screens to identify potential candidate/modifier genes and recently optimized genome editing strategies. These techniques have greatly increased our ability to investigate the impact of certain mutations and how these lesions impact tumorigenesis and disease phenotype. These unique characteristics position the zebrafish as a powerful in vivo tool to model cancer predisposition syndromes and as such, several have already been created, including those recapitulating Li-Fraumeni syndrome, familial adenomatous polyposis, RASopathies, inherited bone marrow failure syndromes, and several other pathogenic mutations in cancer predisposition genes. In addition, the zebrafish platform supports medium- to high-throughput preclinical drug screening to identify compounds that may represent novel treatment paradigms or even prevent cancer evolution. This review will highlight and synthesize the findings from zebrafish cancer predisposition models created to date. We will discuss emerging trends in how these zebrafish cancer models can improve our understanding of the genetic mechanisms driving cancer predisposition and their potential to discover therapeutic and/or preventative compounds that change the natural history of disease for these vulnerable children, youth and adults.